“Recent Advances in the Understanding and Management of Hyperlipidemia: A Comprehensive Review” - Chandra, Richa; Katiyar, Pratima; Kushwaha*, Kalpana (Cuestiones de Fisioterapia, 2025)
Hyperlipidemia has historically been an abnormal condition in which plasm lipoproteins carrying triglycerides, cholesterol, and phospholipids increase to their normal range. This elevation in lipoproteins leads to the risk of cardiovascular diseases including stroke cardiac arrest, atherosclerosis, and other metabolic disorders. It lowers levels of High-Density Lipoprotein while raising Low-Density Lipoprotein levels. There are two forms of hyperlipidemia, Primary and Secondary. The main contributory factor of Primary hyperlipidemia is a genetic disorder called familial, and Secondary hyperlipidemia is due to health conditions like hypothyroidism, obesity, diabetes, long-term alcohol use, and beta-blockers medication use. This medical condition can be managed by a change in lifestyle in combination with pharmacotherapy to control lipid levels. Additionally, with conventional treatment, drug delivery technique innovation has a major influence on hyperlipidemia treatment. This review article focuses on this disease and various forms of hypolipidemic drugs and also covers topics including symptoms, pathophysiology, risk factors, and management. Treatment and prevention strategies include diagnosis, prescribed medication, increased physical activity, eating a healthy diet, monitoring, medical therapy, and reassessing. There has been discussion of recent advancements in new research on diagnosing and managing this disorder. Future directions, for novel drug technology are discussed as well to provide more ideas for improving the safety and treatment of patients.